Implementation Of The SAW Method For Proposing KIS-PBI Recipients In Padang Sari Village - Guntur Maha Putra; Hainur Rasyid (Smart Education, 2026)
Abstract: Determining recipients of health assistance at the village level often faces obstacles of subjectivity and inaccuracy of targeting due to the proposal process which is still carried out manually without structured assessment criteria. This study aims to apply the Simple Additive Weighting (SAW) method in determining recipients of the Indonesian Health Card - Contribution Assistance Recipient (KIS-PBI) in Padang Sari Village to improve the accuracy and objectivity of the proposal process. The method used is a computer-based Decision Support System with a Multiple Attribute Decision Making (MADM) approach, where the assessment is carried out based on a number of predetermined social and economic criteria and is weighted according to their level of importance. The calculation process is carried out through the formation of a decision matrix, matrix normalization, and calculation of preference values for each alternative. The results of the study indicate that the application of the SAW method is able to produce a clear ranking of alternatives, thus facilitating the determination of residents who are eligible to be proposed as KIS-PBI recipients. The conclusion of this study is that the SAW method is effective for use as a decision-making tool in the distribution of health assistance at the village level because it is able to produce more objective, transparent, and measurable decisions compared to the manual method.Keyword: kis-pbi; multiple attribute decision making (MADM); simple additive weightingÂ Abstrak: Penentuan penerima bantuan kesehatan di tingkat desa seringkali menghadapi kendala subjektivitas dan ketidaktepatan sasaran akibat proses pengusulan yang masih dilakukan secara manual tanpa kriteria penilaian yang terstruktur. Penelitian ini bertujuan untuk menerapkan metode Simple Additive Weighting (SAW) dalam penentuan penerima Kartu Indonesia Sehatâ€“Penerima Bantuan Iuran (KIS-PBI) di Desa Padang Sari guna meningkatkan ketepatan dan objektivitas proses pengusulan. Metode yang digunakan adalah Sistem Pendukung Keputusan berbasis komputer dengan pendekatan Multiple Attribute Decision Making (MADM), di mana penilaian dilakukan berdasarkan sejumlah kriteria sosial dan ekonomi yang telah ditetapkan dan diberi bobot sesuai tingkat kepentingannya. Proses perhitungan dilakukan melalui pembentukan matriks keputusan, normalisasi matriks, dan perhitungan nilai preferensi untuk setiap alternatif. Hasil penelitian menunjukkan bahwa penerapan metode SAW mampu menghasilkan perankingan alternatif secara jelas sehingga memudahkan penentuan warga yang layak diusulkan sebagai penerima KIS-PBI. Simpulan dari penelitian ini adalah bahwa metode SAW efektif digunakan sebagai alat bantu pengambilan keputusan dalam penyaluran bantuan kesehatan di tingkat desa karena mampu menghasilkan keputusan yang lebih objektif, transparan, dan terukur dibandingkan dengan metode manual.Kata kunci: kis-pbi; multiple attribute decision making (MADM); sistem pendukung keputusan